Pressure monitoring during lipofilling procedures - Klein, S. M.; Prantl, L.; Geis, S.; Eisenmann-Klein, M.; Dolderer, J.; Felthaus, O.; Loibl, M.; Heine, N. (Clinical hemorheology and microcirculation, 2014)
BACKGROUND: Grafting of autologous lipoaspirate for various clinical applications has become a common procedure in clinical practice. With an estimated mortality rate of 10-15 percent, fat embolism is among the most severe complications to be expected after lipofilling therapies. OBJECTIVE: The aim of this study was to determine the level of interstitial pressure after the injection of defined volumes of lipoaspirate into the subcutaneous tissue of female breasts. It was hypothesized, that interstitial pressure levels exceed the physiologic capillary pressure during lipofilling procedures and hence increase the potential risk for fat embolism. Further it was investigated if external tissue expansion has the potential to significantly reduce interstitial tissue pressure. METHODS: Interstitial pressure was monitored in 36 female patients, that underwent autologous fat injections into the breast. Measurements were conducted with a sensor needle connected to a pressure transducer (LogiCal Pressure Monitoring Kit, Smiths medical int. Ltd., UK). Patients were divided into 4 subcohorts differing in their pre-treatment regimen or local tissue conditions. Pre-treatment consisted of tissue expansion, achieved with the Brava™ (Brava LLC Miami, Fla., USA) vacuum-chamber. RESULTS: The increase in interstitial pressure after injection volumes of 100 ml (p = 0.006), 200 ml (p = 0.000) and between 100 ml and 200 ml (p = 0.004) respectively, were significant in non-mastectomized patients without pre-treatment. Patients pre-treated with Brava™ did not show such statistically significant differences in interstitial pressures before and after the injection of 100 ml and 200 ml of lipoaspirate (p = 0.178). The difference in interstitial pressure in mastectomized patients between 0 ml and 100 ml (p = 0.003), as well as 0 ml and 200 ml (p = 0.028) was significant. The difference in pressures between pre-treated patients and patients without pre-treatment did not differ significantly in the mastectomized patient cohort. CONCLUSION: During lipofilling procedures interstitial pressures are reached that exceed pressure limits defined as hazardous for fat embolism. To date it is unknown what pressure levels need to be considered critical for complications in soft tissue interventions. Further the results indicate higher interstitial pressures for patients that had undergone mastectomy, whereas pre-treatment with external tissue expansion seemed to diminish pressure values.
CRIS-Team Scopus Importer:2024-12-11
Keywords: Brava; fat embolism syndrome; Lipofilling; pressure monitoring